The gender gap in educational outcomes in Norway - Borgonovi, Francesca (OECD Publishing, 2018)
As is the case in most OECD countries, boys in Norway are more likely to have lower levels of academic achievement and attainment than girls. While this phenomenon is not recent, it has become increasingly pronounced in recent years and, as a result, is attracting considerable attention from policy-makers in many countries. This paper develops evidence of gender gaps in educational outcomes in Norway and selected OECD countries and identifies examples of policies and practices that could help close existing gender gaps in Norway. The first part of the paper describes gender gaps in school achievement, attainment, attitudes, beliefs and behaviours using an international comparative analysis. Evidence from PIRLS, TIMSS, PISA and the OECD Survey of Adult Skills (PIAAC) is used to identify gender gaps during primary and secondary schooling as well as young adulthood. The second part of the paper summarises evidence on policies and practices that were implemented in other countries and that could support efforts in Norway to mitigate, prevent and reduce gender gaps in achievement and attainment. Most of the evidence on policies and practices reviewed in the report comes from the peer countries Finland, the Netherlands and the United States that were identified of particular relevance for Norway, given the policy challenge Norway faces
Keywords: Education; Norway